Floodplain and hydraulic infrastructure system modeling for integrated flood management - Hii, Ching Poon (Universiti Malaysia Sarawak, (UNIMAS), 2010)
en recent years, river floods in Sarawak River seemed to occur more frequently and had been causing more and more economic and social damages. One of the greatest deficiencies of the current flood management system for Sg. Sarawak basin is its inadequate optimization of the existing structural measures. This optimization may be achieved by application of some of the models and the framework developed recently for enhancement of participation of various local stakeholders in flood management.) Hydrological simulations had been conducted and carried out using HEC-HMS for Sg. Sarawak catchment. The model was calibrated and validated using years 1976 and 2000 flood events. The rainfall - runoff hydrographs generated from calibration and validation processes showed Nash-Sutcliffe values of 0.78 and 0.71, respectively. Sensitivity analysis was perfonned to examine the impacts of the three parameters, namely, initial loss, constant loss and lag time parameters on the HECHMS hydrological model. The analysis revealed that the initial loss parameter acted as the most sensitive parameter with respect to peak flow and total runoff volume. It was also found that an increase in constant loss could result in a lower peak, while the lag time was the most sensitive parameter with respect to peak time. ~ . However, lag time parameter was found to be the least sensitive among the three parameters tested. The calibrated hydrological model was then used as inflow hydrographs in InfoWorks RS model. Two hydraulic models, namely, Pre-barrage Sg. Sarawak Model and Post-barrage Sg. Sarawak Model were developed, calibrated and validated by modifying Manning's n values corresponding to field observations. 111 Years 1976 and 2000 flood events were used for calibration and validation purposes, and showed to have an accuracy of approximately 90% for both processes. Sensitivity analysis was carried out to investigate the impact of Manning's n on the water levels. Manning's n sensitivity was tested using values ranging from 0.025 to 0.055. The results revealed that the peak water level was not sensitive to Manning's n values. The hydraulic model was intended to integrate the existing flood mitigation structures available in Sg. Sarawak Basin. Two Scenarios: 1) Sarawak River basin-wide modeling and 2) Flood Bypass Channel modeling were carried out using the models developed for this research to investigate the performance of the existing flood mitigation measures in Sg. Sarawak basin. The results revealed that the existing structure, Sg. Sarawak barrage was able to trim down the backwater due to King Tide or the flood flow from the upstream. However, the barrage had insignificant on water level during king tide and flood event. The modeled results were used in Logical Framework Analysis to look into the possible alternatives that may help reduce the damage. The outcomes of this study showed that the existing condition could be significantly improved once the Flood Bypass Channel and Early Flood Warning System are constructed. Flood Bypass Channel modeling was carried out to determine the impact of the proposed alternatives on the existing conditions of Sg. Sarawak Basin. In this scenario, a flood bypass channel and an additional barrage are proposed to divert the excess flood water from Kuching City in the event of severe flood. It was shown that flooding problems in Kuching can be significantly reduced. However, the areas located upstream of Kuala Maong could still be subjected to flooding. Early Flood Warning system could be provided to evacuate the floodplain dwellers before severe floods strike. An analytical logical framework for Early Flood Warning System IS presented in this dissertation. The models and methods developed in this study are flexible and easy for Sg. Sarawak Basin. In this research, both the feasibility of and effectiveness in incorporating the premise of the combined technical information and institutional setup in flood management are addressed.